2013
DOI: 10.1111/tbed.12147
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary and Ecological Dynamics of Transboundary Disease Caused by H5N1 Virus in Southeast Asia

Abstract: Southeast Asia has been the breeding ground for many emerging diseases in the past decade, and it is in this region that new genetic variants of HPAI H5N1 viruses have been emerging. Cross-border movement of animals accelerates the spread of H5N1, and the changing environmental conditions also exert strong selective pressure on the viruses. The transboundary zoonotic diseases caused by H5N1 pose a serious and continual threat to global economy and public health. Here, we divided the H5N1 viruses isolated in So… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 40 publications
1
14
0
Order By: Relevance
“…In addition, all Indonesian viruses ( n = 44), including clades 2.1.1, 2.1.2, 2.1.3 and its subclades, formed an independent branch with a high bootstrap value. All Vietnamese viruses (clades 1, 2.3.2, 2.3.4 and their subclades) had evolved into two distinct branches as previously reported (Wei et al., ). One is composed of clades 1 and 1.1 viruses, and the other consists of clades 2.3.3, 2.3.4 and their subclades viruses.…”
Section: Resultssupporting
confidence: 57%
See 1 more Smart Citation
“…In addition, all Indonesian viruses ( n = 44), including clades 2.1.1, 2.1.2, 2.1.3 and its subclades, formed an independent branch with a high bootstrap value. All Vietnamese viruses (clades 1, 2.3.2, 2.3.4 and their subclades) had evolved into two distinct branches as previously reported (Wei et al., ). One is composed of clades 1 and 1.1 viruses, and the other consists of clades 2.3.3, 2.3.4 and their subclades viruses.…”
Section: Resultssupporting
confidence: 57%
“…Successful culling of all poultry in Hong Kong seemed to have controlled the outbreaks, but additional H5N1 viruses in 1999 and 2001 revealed that variants of the virus continuously circulate in this region (Cauthen et al., ; Wei et al., ). In late 2003 and early 2004, HPAI H5N1 outbreaks recurred with unexplained reasons and the viruses spread persistently to poultry species in China and many South‐East Asian countries, such as Vietnam, Cambodia, Thailand and Indonesia, causing sporadic transmission to humans and catastrophic damage to the poultry industry (Wei et al., ). The movements of wild birds and trade in domestic poultry and wild birds may serve as potential agents for the global dispersion of HPAI H5N1 viruses (Fang et al., ), and other factors such as environment also play a vital role in the occurrence and spread of HPAI H5N1 viruses (Fang et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…Cases of human infection with swine‐origin A(H3N2) and variant A(H3N2)v are a public health concern in North America, and human A(H3N2)v infection has been suggested to be associated with agricultural fairs where people get in close contact with infected pigs (Lindstrom et al., ; Jhung et al., ). Other parts of the world, such as South‐East Asia, are regarded priority areas for influenza surveillance, due to the high density and the complex interactions between humans, pigs, poultry and agricultural land (Wei et al., ). Since 2003, South‐East Asia has experienced high pressure from the HP H5N1 virus, resulting in the death or destruction of more than 175 million birds and in 463 human cases, including 318 deaths (Pfeiffer et al., ; World Health Organization, ,b).…”
Section: Introductionmentioning
confidence: 99%
“…Alternatively, early in the H5N1 highly pathogenic avian influenza (HPAI) panzootic, wild bird migration was offered as a key amplifier. Latterly, the illegal global trade in poultry was found to be a more potent factor in spread (Wei et al, 2013).…”
Section: Synergists Amplifiers and Mitigatorsmentioning
confidence: 99%